Under the bridge: marking sites prove the presence of Eurasian otter Lutra lutra in the Poljanska Sora River valley, Slovenia - Rudi Kraševec; Aleksander Trajbarič; Urša Fležar (Natura Sloveniae)
Knowledge on distribution of the Eurasian otter (Lutra lutra) in Slovenia in the past was very limited, due to the lack of studies of this species. Hunting and persecution reduced the species distribution area and densities. After its legal protection in 1973, the species seems to have increased in population size. A few studies had shown the Eurasian otter repopulating the Alpine region. To confirm the presence of the species in the Slovenian Pre-Alps, we searched for otter scat – spraint, on six tributaries to the Poljanska Sora River of Polhograjsko hribovje, the Pre-Alpine mountains around Polhov Gradec. Otter marking sites were exclusively in the riverbed (100 %), with a great majority found under the bridges (83 %). Using camera traps, we were able to collect video evidence of the otter reproduction and confirm that the species is reproducing in the studied region. Since this area could act as a corridor for the otter’s recovery in the Adriatic River basin, it is crucial to continue to monitor its presence and the potential expansion to the west of the country.